The ameliorating effect of withaferin A on high-fat diet-induced non-alcoholic fatty liver disease by acting as an LXR/FXR dual receptor activator - Shiragannavar, Varsha D.; Sannappa Gowda, Nirmala G.; Puttahanumantharayappa, Lakshana D.; Karunakara, Shreyas H.; Bhat, Smitha; Prasad, Shashanka K.; Kumar, Divya P.; Santhekadur, Prasanna K. (Frontiers in Pharmacology, 2023)
Recently, Non-alcoholic Fatty liver disease (NAFLD) incidences are rapidly increasing and it has emerged as one of the major diseases of the modern world. NAFLD constitutes simple fatty liver to chronic non-alcoholic steatohepatitis (NASH) which often leads to liver fibrosis or cirrhosis, a serious health condition with limited treatment options. Many times, NAFLD also progresses to fatal hepatocellular carcinoma (HCC). Nuclear receptors (NRs) like Liver X receptor-α (LXR-α) and closely associated Farnesoid X receptor (FXR) are ligand-inducible transcription factors that regulate various metabolism-associated gene expressions also repression and play a major role in controlling the pathophysiology of the human liver. Withaferin A is a multifaceted potent dietary natural compound with huge beneficial properties and plays a vital role as an anti-inflammatory molecule. Recently, we have shown Withaferin A as a new ligand and a novel modulator of LXR-α in HCC. Here, we further explored the dual receptor activating nature of Withaferin A by docking studies, which potently improves high-fat diet-induced NAFLD in mice and suppresses diet-induced hepatic inflammation and liver fibrosis via LXR/FXR. Our in vitro studies also indicate that Withaferin A inhibits lipid droplet accumulation in Sodium palmitate and Oleate treated HepG2 and Huh7 cells possibly through LXR-α and FXR-mediated signaling pathways. Withaferin A is a known inhibitor of NF-κB mediated inflammation. Withaferin A treatment significantly inhibited TGF-β-induced gene expression, which contributes to reduced hepatic fibrosis. Intriguingly, both LXR and FXR activation inhibits inflammation and fibrosis by negatively regulating NF-κB. Thus, the LXR/FXR dual receptor activator Withaferin A improves both NAFLD-associated liver inflammation and fibrosis in mice models as well as under in vitro conditions, which makes Withaferin A the possible potent pharmacological and therapeutic agent for the treatment of diet-induced NAFLD.